2021
DOI: 10.3171/2019.9.jns191646
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation in the caudal zona incerta in patients with essential tremor: effects on cognition 1 year after surgery

Abstract: OBJECTIVEThe ventral intermediate nucleus (VIM) of the thalamus is currently the established target in the use of deep brain stimulation (DBS) to treat essential tremor (ET). In recent years, the caudal zona incerta (cZi), a brain target commonly used during the lesional era, has been revived as the primary target in a number of DBS studies that show evidence of the efficacy of cZi targeting in DBS treatment for controlling the symptoms of ET. The authors sought to ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…We next investigated the predictive power of the hypointensity with respect to clinical improvement and compared the model's performance to correlations with hotspot, coldspot, VIM, DRT, and other structures that have been implicated in tremor suppression, namely pallidothalamic tract 31 and caudal ZI (cZI). 32,33 To this end, simple linear models were generated investigating the relationship between percent volume overlap and clinical improvement scores obtained at 12 months compared to preoperative baseline (see Fig 3). Overlap between each patient's stimulation volume and the hypointensity template significantly correlated with clinical improvement (R 2 = 0.16, p = 0.017).…”
Section: Validation Of Probabilistic Mappingmentioning
confidence: 99%
“…We next investigated the predictive power of the hypointensity with respect to clinical improvement and compared the model's performance to correlations with hotspot, coldspot, VIM, DRT, and other structures that have been implicated in tremor suppression, namely pallidothalamic tract 31 and caudal ZI (cZI). 32,33 To this end, simple linear models were generated investigating the relationship between percent volume overlap and clinical improvement scores obtained at 12 months compared to preoperative baseline (see Fig 3). Overlap between each patient's stimulation volume and the hypointensity template significantly correlated with clinical improvement (R 2 = 0.16, p = 0.017).…”
Section: Validation Of Probabilistic Mappingmentioning
confidence: 99%
“…Fytagoridis et al (2013) found while DBS adversely influenced the verbal fluency immediately after surgery when compared against a baseline, this effect dissipated at 1 year both on and off stimulation suggesting the deterioration likely reflected a micro-lesion effect. In a study involving caudal zona incerta stimulation, although the overall cognitive functioning was stable, there was a slight but statistically significant decline in semantic fluency at a 1-year follow-up (Philipson et al, 2019). A few studies have also shown improvement of cognitive functioning for ET with DBS besides the earlier work by Tröster et al (1999).…”
Section: Discussionmentioning
confidence: 94%
“…The detailed characteristics of included studies are shown in Table 1 . For sensitivity analysis, eight studies were included in the PSA‐DBS group 13 , 22 , 23 , 24 , 25 , 26 , 27 , 28 and fourteen studies were included in the VIM‐DBS group. 5 , 6 , 13 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 Due to the short term of follow‐up, three studies in the VIM‐DBS group were excluded from the main analysis.…”
Section: Resultsmentioning
confidence: 99%
“…According to multiple reports, VIM‐DBS improves the QoL in ET patients. However, only five studies reported the QoL of PSA‐DBS using three different types of assessment scales, including SF‐36, ADL, and QUEST 13,22,24,27,28 . It is of limited value to use such diverse data to make a comparison with VIM‐DBS.…”
Section: Discussionmentioning
confidence: 99%